Christian Monuments of Cyrenaica - Ward-Perkins, J.B. (BILNAS British Institute for Libyan & Northern African Studies, 2024)
Christian Monuments of Cyrenaica publishes archaeological studies undertaken between 1953 and 1971 by the late J. B. Ward-Perkins (d. 1981) and the late R. G. Goodchild (d. 1968). It presents Ward-Perkins accounts (mostly left in advanced draft form) of 44 monuments, 35 of them certainly churches, together with plans of each made by professional architects after survey on the ground, drawings of some details and a considerable number of photographs, together with a draft overview of the buildings techniques used. Colleagues have provided introductory notes on other major features of the buildings and drawn attention to some of the problems that they raise. They have also added a brief account of other Christian buildings reported since Ward-Perkins' last visit to Cyrenaica, both in Cyrenaica itself, the late antique province of Libya Superior, and in that area of the Western Desert which formed the closely-related province of Libya Inferior.The detailed evidence collected here represents a basis for the study of late antique and early Byzantine Cyrenaica of a quality and extent that has never been available before; and is all the more important because time and chance have now damaged some of that evidence. It also gives a quite up-to-date, although very summary account of new evidence awaiting serious study; which, we may hope, will lead to further advances in our understanding of the late antique and early Byzantine periods.